Metal–ligand–Lewis acid multi-cooperative catalysis: a step forward in the Conia-ene reaction. Issue 1 (6th November 2020) - Clerc, Arnaud; Marelli, Enrico; Adet, Nicolas; Monot, Julien; Martín-Vaca, Blanca; Bourissou, Didier
Abstract : An original multi-cooperative catalytic approach was developed by combining metal–ligand cooperation and Lewis acid activation. Abstract : An original multi-cooperative catalytic approach was developed by combining metal–ligand cooperation and Lewis acid activation. The [(SCS)Pd]2 complex featuring a non-innocent indenediide-based ligand was found to be a very efficient and versatile catalyst for the Conia-ene reaction, when associated with Mg(OTf)2 . The reaction operates at low catalytic loadings under mild conditions with HFIP as a co-solvent. It works with a variety of substrates, including those bearing internal alkynes. It displays complete 5- exo vs. 6- endo regio-selectivity. In addition, except for the highly congested t Bu-substituent, the reaction occurs with high Z vs. E stereo-selectivity, making it synthetically useful and complementary to known catalysts.